2018
DOI: 10.18502/kss.v3i9.2716
|View full text |Cite
|
Sign up to set email alerts
|

E-literary Texts: Reading Materials for School Literacy Movement

Abstract: This research aimed to describe the efforts to provide good and appropriate e-literary texts and for reading material for the school literacy movement, and describe implementation and significance that students should obtain in relation to the mentioned objective. A qualitative descriptive method was used. The data collection techniques used were documents, in-depth interviews, and recordings. The validity of the data is checked by triangulation of data, researcher, method as well as theories.The data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
7
0
2
Order By: Relevance
“…Short stories are the best material in teaching [23]. However, schools also use e-literary texts as a material for this program by providing the material needed [24]. On this basis, the school created a program to add 1,000 books to support this literacy movement at Al Mujahidin Muhammadiyah Middle School.…”
Section: Development Of School Literacy Movementsmentioning
confidence: 99%
“…Short stories are the best material in teaching [23]. However, schools also use e-literary texts as a material for this program by providing the material needed [24]. On this basis, the school created a program to add 1,000 books to support this literacy movement at Al Mujahidin Muhammadiyah Middle School.…”
Section: Development Of School Literacy Movementsmentioning
confidence: 99%
“…The reading activity for elementary school students equals is expected to become the habit of students (Zasacka, 2017). This habit will encourage students' curiosity about each of their reading material (Saito et al, 2015;Setiyadi, 2018). Reading for approximately fifteen minutes with a variety of methods is believed to arouse the students' enthusiasm and memory capacity (Lastiningsih et al, 2017;Shipstead, Lindsey, Marshall, & Engle, 2014).…”
Section: Literacy Movement Achievementsmentioning
confidence: 99%
“…Reading habit is expected to be able to initiate students to produce productive work (Setiyadi, 2018;Tsuneyoshi, 2012). Students' productive work includes summaries of results from the reading material.…”
Section: Literacy Movement Achievementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contradictsSlovaček et al (2017) who suggested that teachers need to use creative method or technique to teach literacy.All teachers encouraged their students to use other reading sources, from internet, video and others, for their learning activities. The learning sources for literacy activity can be obtained from various sources, not only buying the books or any other texts or borrowing them from library, but also accessing to internet(Setiyadi, 2017) [7]. Thisrequires the teachers to integrate the technology use (Alvermann & Hagood, 2000; Hutchison & Reinking, 2011; Leu et al, 2012 in Pitcher & Mackey, 2013).…”
mentioning
confidence: 99%